Evaluation of the patients' satisfaction on pharmaceutical pictogram provided in a Polish community pharmacy - pilot study - Adrianna Narożny; Szymon Zdanowski; Damian Świeczkowski; Miłosz Jaguszewski; Jerzy Krysiński; PIOTR MERKS (Polish Pharmaceutical Society, 2020)
Background: Pharmaceutical pictograms are useful tools aimed to improve patients' understanding of medical information. They can be easily implemented into routine settings and can embrace various information, among others, about drug regimen, drug adverse reactions, and potentially harmful drug interactions. Since pharmaceutical pictograms can improve patients' knowledge, they can also improve adherence to recommended therapy. Thus, it is wise to understand patients' perspectives on pictograms, particularly due to the cultural discrepancies existing between populations in which pharmaceutical pictograms are used. Aim: The aim of the study was to collect patients' perspectives particularly in terms of satisfaction on the pharmaceutical pictograms used in routine community pharmacy settings. Materials and methods: The study is immersed in a quantitative approach. The survey, based on an authorial questionnaire, was conducted in a single community pharmacy in the north part of Poland. Labeling was conducted by qualified professional staff according to validated recommendations provided via a computer system. 103 questionnaires were collected and analyzed. Only adult patients participated in the study. Results: Almost all participants (96.11%) acknowledged that such a labeling system could be helpful in following the physicians' recommendations and can overall simplify the use of medicines. Additionally, 84.47% of patients stated that pictogram labels should be applied to both prescription and over-the-counter drugs. The vast majority (91.26%) also did agree that pharmaceutical pictograms should be available in every community pharmacy. Statistical analysis showed that patients who stated that pharmaceutical pictograms should be available in every community pharmacy and be provided on a patient demand were those for whom drug leaflets were not always understandable. Conclusions: Patients positively evaluated pharmaceutical pictograms. Further studies are warranted, particularly more representative in order to determine the most optimal direction for the development of pharmaceutical services in Poland.